Alternate Land Use Strategies for Income Maximisation of Tropical Homegardens - Regeena, S.; Ravi, S.; Jayasree, G.S. (Indian Journal of Agroforestry, 2020)
Surveys conducted in the South Zone of Kerala during the year 2002-03 under the National Agricultural Technology Project on Homestead Farming revealed that a major part of the homesteads of the zone were mismanaged and thus could not realize their full potential in productivity or profitability. An attempt was done under the project to formulate integrated farm models which could provide maximum benefits to the farmer. Five such models for a farm of approximately 0.4 ha in size, located in the coastal agro-ecosystem are presented and analysed in this paper. The analysis clearly reveals that the productivity and profitability of home gardens can be substantially increased by scientific planning and management.